Leading causes of death and concomitant pathology in patients with type 2 diabetes mellitus according to autopsy data - Anna Leont'evna Terekhova (Endocrinology Research Centre, 2011)
Aims. The aim of this study was to estimate the prevalence rate of concomitant pathology and its influence on leading causes of death in patients withtype 2 diabetes mellitus according to clinical charts and pathologist's reports. Materials and methods. We have studied the database of Moscow City Hospital №50 in order to pick out confirmed cases of type 2 DM, treated inthe period from 2006 to 2008 years (302 patients, 9,97%). Prevalence rate of concomitant pathology and leading causes of death were then carefullystudied on this ground. Results. We examined clinical charts of 302 patients with type 2 DM - 219 female (72.5%) at the age of 76 [70;80] and 83 male at theage of 75 [68;80]. Cardiovascular pathology and cerebrovascular disease (acute cerebrovascular event and/or postinfarction encephalic cysts,discirculatory encephalopathy) (50.66%) showed high prevalence. Respiratory system diseases (25.8%), excessive body weight and obesity (21.5%),gallstone disease (19.86%), malignant neoplasm (16.2%), prostatic hyperplasia (found in 35 male patients, 42.17%), gynecologic pathology (foundin 23 female patients, 10.5%) and infectious inflammatory diseases of kidneys and urinary tract (8.6%) were also disclosed. Leading causes of deathwere found to be acute cerebrovascular events (28.8%), postinfarction cardiosclerosis (23.18%), acute/recurring myocardium infarction (19.54%)and malignant neoplasm (14.57%). High polypathy prevalence was discovered in studied cohort, and in one third of cases patients perished fromcombination of concurrent diseases.Conclusion: High prevalence rate of intercurrent diseases and polymorbidity in patients with type 2 diabetes mellitus substantiate the need for thoroughexamination at different stages of medical care, treatment of existing malfunctions, as well as preventive measures against complications.